Carriers Based on Zein-Dextran Sulfate Sodium Binary Complex for the Sustained Delivery of Quercetin - Wang, Tian-xing; Li, Xiao-xi; Chen, Ling; Li, Lin; Janaswamy, Srinivas (Frontiers in Chemistry, 2020)
Herein, a self-assembly formulation of Zein and dextran sulfate sodium (DSS) binary complex has been developed for the quercetin (Que) delivery. The prepared particles display smooth sphere in a range of 180~250 nm. The addition of DSS shields Trp residues of Zein that were located on the hydrophilic exterior and in-turn reduces the surface hydrophobicity of the nanoparticles. The presence of DSS, indeed, increases the encapsulation efficiency of Que from the initial 45.9 in the Zein to 72.6% in the Zein/DSS binary complex. Significant reduction of Que diffusion in the simulated intestinal conditions has been observed with the addition of DSS on to the nanoparticles, which also improves Que bioavailability. The release mechanism of Que-loaded Zein/DSS composites is in accordance with Higuchi model (Q=0.0913t0.5+0.1652, R2=0.953). Overall, nanoparticles based on Zein-DSS complexes stand out to be an attractive carrier system of quercetin and the outcome could be extended to several bioactive compounds.